Pengembangan Tanaman Hidroponik Dengan Sistem Pengisi Air Otomatis Menggunakan Arduino Uno Di Kelurahan Senggarang - AGUSTINA SARTIKA YOS EKARISTI MANIK; SEPLI YANDRI; DWI CAHYA RADA (CV. Akira Java Bulu, 2025)
The development of an automatic hydroponic system in the Senggarang area, Tanjungpinang began with regional observation and interviews at the Senggarang Village Office to identify existing problems and potentials. The purpose of developing hydroponic plants with automatic water fillers is to reduce public expenditure on buying food, especially vegetable ingredients, and minimize places to grow crops. The method used in the development of hydroponic plants with automatic water filling uses a descriptive method. The implementation of an automatic water filling system using Arduino Uno, relays, water pumps, and ultrasonic sensors has shown satisfactory results. The system works consistently by turning off the pump when the water level reaches 2-3 cm and turning it back on when the water level drops to 11 cm. The test results showed a stable reading with the pump off at a distance of 2.07 cm and on at a range of 11.17-11.63 cm prove that the system can work effectively without manual supervision.